Frequency of cholecystectomy and associated sociodemographic and clinical risk factors in the ELSA-Brasil study - Alves, Kamila Rafaela; Goulart, Alessandra Carvalho; Ladeira, Roberto Marini; Oliveira, Ilka Regina Souza de; Benseñor, Isabela Martins (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: There are few data in the literature on the frequency of cholecystectomy in Brazil. The frequency of cholecystectomy and associated risk factors were evaluated in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). DESIGN AND SETTING: Cross-sectional study using baseline data on 5061 participants in São Paulo. METHODS: The frequency of cholecystectomy and associated risk factors were evaluated over the first two years of follow-up of the study and over the course of life. A multivariate regression analysis was presented: odds ratio (OR) and 95% confidence interval (95% CI). RESULTS: A total of 4716 individuals (93.2%) with information about cholecystectomy were included. After two years of follow-up, 56 had undergone surgery (1.2%: 1.7% of the women; 0.6% of the men). A total of 188 participants underwent cholecystectomy during their lifetime. The risk factors associated with surgery after the two-year follow-up period were female sex (OR, 2.85; 95% CI, 1.53–5.32), indigenous ethnicity (OR, 2.1; 95% CI, 2.28–15.85) and body mass index (BMI) (OR, 1.10; 95% CI, 1.01–1.19 per 1 kg/m2 increase). The risk factors associated over the lifetime were age (OR, 1.03; 95% CI, 1.02–1.05 per one year increase), diabetes (OR, 1.92; 95% CI, 1.34–2.76) and previous bariatric surgery (OR, 5.37; 95% CI, 1.53–18.82). No association was found with parity or fertile age. CONCLUSION: Female sex and high BMI remained as associated risk factors while parity and fertile age lost significance. New factors such as bariatric surgery and indigenous ethnicity have gained importance in this country.